PENERAPAN STRUCTURED DYADIC METHODS (SDM) BERBANTUAN MEDIA TUTORIAL UNTUK MENINGKATKAN HASIL BELAJAR SISKOMDIG PADA SISWA KELAS X MM1 DI SMKN 1 KRAKSAAN - Dewi Wahyuning Hikmah (Al-Fikru : Jurnal Pendidikan Dan Sains, 2020)
School is a place where a student experiences the learning process. In this learning process, there are several subjects that require each student to understand the material in these subjects. The research method used is a qualitative method with CAR analyzed descriptively by using the percentage technique to see trends that occur in learning activities. The application of the Structured Dyadic Methods (SDM) learning method assisted by tutorial media can improve and increase student activity and learning outcomes. The Structured Dyadic Methods (SDM) learning method assisted with tutorial media can make students build their own knowledge, find steps in finding solutions to a material that must be mastered by students, both individually and in groups Keywords: HR, Media Tutorial, Siskomdig